A PROPANOL GAS MEASUREMENT SYSTEM USING A QUARTZ CRYSTAL MICROBALANCE AS A MASS SENSOR - Budianto, Arif (Journal of Environmental Engineering and Sustainable Technology, 2022)
Propanol gas is an alcohol compound classified as a volatile organic compound (VOC). This gas can be classified as air pollution with a harmful impact on human health. There is an urgent need to minimize the health impact by mitigating propanol gas concentration. There is limited information about propanol gas measurement. Therefore, developing a propanol gas measurement device with high sensitivity and selectivity is necessary. Hence, this study developed a propanol gas concentration measurement system based on a bare quartz crystal microbalance. This crystal was placed inside an experimental chamber and exposed to propanol gas. The crystal frequency shift was measured using a frequency counter. The results show that the propanol gas concentration is linearly correlated to the frequency shift resulting in the crystal with a regression coefficient of R2 > 0.75). The system can measure propanol concentrations <1 μg.L-1 with a sensitivity of 5 Hz.mg.L-1. It can be concluded that a gravimetry-based measurement system using a quartz crystal microbalance has the potential to measure the concentration of propanol gas.